L’intégration de la conservation préventive dans les phases de la programmation architecturale - Stéphanie Kuhn (In Situ)
In spite of all the progress achieved over the past ten years, preventive conservation is still largely considered as a discipline related to the collections strictly speaking, in particular by architects, space planers and other stakeholders involved on a project. Although investigations on preventive conservation have been largely developed, do they have enough effect on architectural and museum projects? How is this discipline integrated within the key phases and especially within the one of architectural and museum planning? What are the stakes of the better preventive conservation integration within different phases of a project to create or redesign a museum? Beyond the planning phase which is a key moment in the process of structuring a project on a museum creation or renovation, what is at stake in the work achieved within the Preventive Conservation Master’s thesis, is to develop problematics about the integration of preventive conservation in the whole process of project management, from the PSC to the equipment delivery, and to objectively identify the key indicators that can have, in the future, a significant influence upon museum institutions operating model, and at last to identify during the project execution the current outline of the integration of both the preventive conservation and its experts. The proposed approach comes within the scope of a project management appraisal.